Carmen [opéra comique in four acts] - Bizet, Georges 1838-1875 (Opus Arte, 2008)
The Spanish gypsy Carmen lives only for sensuality. Love drives her from man to man. She encompasses the sergeant Don José with her wiles, and leads him to mutiny and desertion. Finally nothing remains for him but to join a band of smugglers of which Carmen is a member. His fate is endurable as long as he keeps hold of the love of Carmen, but when she turns from him he is sunk into despair